Development and Validation of an UHPLC-MS/MS Assay for the Therapeutic Monitoring of Brivaracetam Plasma Concentrations in Patients with Epilepsy. Issue 3 (June 2020) - Mohamed, Susan; Riva, Roberto; Contin, Manuela
Abstract : Background: Brivaracetam is an antiepileptic drug used as an add-on therapy for partial-onset seizures in subjects aged 4 years and older. Owing to potential drug interactions and intersubject variability in plasma concentrations, therapeutic monitoring for brivaracetam may be useful. The aim of this study was to develop a simplified method for measuring brivaracetam plasma concentrations applicable to therapeutic drug monitoring in epilepsy. Methods: An ultra high-pressure liquid chromatography–tandem mass spectrometry method was developed and validated according to current guidelines for bioanalytical methods. Sample preparation (100 µL) involved only a simple precipitation step by acetonitrile. Brivaracetam-d7 was used as internal standard. The chromatographic analysis was performed by a Synergi Fusion column using 0.1% formic acid in water/acetonitrile as a binary gradient mobile phase, at a flow rate of 0.3 mL/min. Both brivaracetam and the internal standard eluted at 1.01 minutes. This method was applied to measure trough and 1-hour postmorning dose brivaracetam plasma concentrations of 11 patients with epilepsy. Results: The method was validated over a concentration range of 0.10–10 mcg/mL. The mean recovery was 95%. Both intra- and inter-assay imprecision and inaccuracy were <15% for all quality control samples. The lower limit of quantitation and detection was 0.10 and 0.05 mcg/mL, respectively. No interferences or carry-over was observed. Median (25%–75% quartiles) trough and 1-hour postdosing brivaracetam plasma concentrations were 0.61 mcg/mL (0.47–0.83 mcg/mL) and 1.55 mcg/mL (1.24–2.12 mcg/mL), respectively, at a median dose of 80 mg/d (50–150 mg/d). Large, up to 8-fold, intrasubject fluctuations of brivaracetam concentrations between trough and 1-hour postdosing were observed. Conclusions: The present assay is faster and simpler than previously published analytical reports for brivaracetam in human plasma and is suitable for therapeutic drug monitoring.